[Red Hot Rock at Eldfjell] - Streng, Evelyn Fiedler (1975)
Photograph of red hot rocks on Eldfjell. The red stone covered in grey ash and rocks sit on either side of the photograph, opening up at the center to a dark hole. The jagged interior walls of the rock disappear in the shadow. A wooden stick is on fire in the top left corner of the photograph.